Environmental Sustainability: To Enhance Organizational Awareness towards Green Environmental Concern - Ramli, Yanto; Imaningsih, Erna Sofriana; Shiratina, Aldina; Rajak, Adnan; Ali, Anees Janee (International Journal of Energy Economics and Policy, 2022)
The crude oil waste such as POME is huge destruction to the surrounding community and causes greater harm unleashing several skin issues, toxic infections, and digestion disorders. The issue attracts the attention of scholars; hence, the present study attempts to build an understanding of organizational awareness and how it could solve the stated issue and turn into useful elements such as potential green resources. For this, the study used green environment, innovation management, and environmental concern as an independent variable, orgazanitional awareness as a dependent variable, and environmental sustainability as an intervening variable. This helps scholars and practitioners to solve the said issue which still happens to be unresolved. Moreover, it also helps to prevent further damage to the environment and community. To attain the objective of the study, the authors proposed a framework, and based on prior literature and empirical evidences, seven hypotheses were formulated. The study used purposive sampling and the projected population is the mills that are situated in North Sumatera province of Indonesia. The smart PLS methodology is opted to analyze sample data. The findings reveal that ga reen environment amongst all has a stronger influence on environmental sustainability. The results also indicate that the firms need to consider the innovative ideas and build innovative teams which could help them to transform the disrupted POME into valuable green resources. At the end, the study also offers some implications and future recommendations which if considers, would add a valuable contribution in the existing literature.